Anti-PL-7/PL-12 antisynthetase syndrome associated with interstitial lung disease following SARS-COV-2 infection and vaccination: A case study review - Laura García-Bravo; Ángela Villegas; Bárbara López Uceda; Anaís Mariscal; Cristina Vadillo; M Asunción Nieto Barbero; Juan Luis Rodríguez-Hermosa; Beatriz Mediero Valeros; José Carlos Plaza-Hernández; Miguel Fernández-Arquero; María Guzmán-Fulgencio; Gloria Candelas-Rodríguez; et al. (Heliyon)
Cumulative evidence suggests a link between specific autoimmune diseases (AD), including idiopathic inflammatory myopathies (IIM), and SARS-CoV-2 infection or COVID-19 vaccination. Anti-synthetase syndrome (ASS), a subset of IIM, is defined by the presence of autoantibodies against aminoacyl-tRNA synthetase (anti-ARS) and is strongly associated with interstitial lung disease (ILD), a major contributor to severe complications and reduced survival. We present four clinical cases of patients who developed autoantibodies against threonyl (PL-7) and alanyl (PL-12) synthetases associated with ASS-ILD shortly after SARS-CoV-2 infection or COVID-19 vaccination. Anti-ARS autoantibodies were identified using three complementary methods: immunoblotting, western blotting (WB) and the method considered the gold standard, immunoprecipitation (IP), which ensures accurate interpretation of results. The study highlights the clinical and pathogenic overlap between ASS-ILD and SARS-CoV-2-related lung involvement.Both conditions share similar high-resolution computed tomography (HRCT) patterns, including inflammation and pulmonary fibrosis (PF), driven by IFN-γ signaling, which complicates accurate diagnosis. Our results provide novel insights into the temporal association of SARS-CoV-2 and vaccine exposure with ASS-ILD, focusing on possible molecular mimicry between viral proteins and ARS molecules as a potential mechanism. Understanding the involvement of specific anti-ARS autoantibodies (PL-7 and PL-12) and the identification of genetic predispositions (HLA-B∗08:01 and HLA-DRB1∗03:01) in these patients may be key to underpinning these autoimmune manifestations. The study underscores the importance of a multidisciplinary approach and vigilant follow-up to optimize diagnosis and management. Further research is essential to elucidate the causal relationships and molecular mechanisms behind these observations.